2019
DOI: 10.4102/sajpsychiatry.v25i0.1339
|View full text |Cite|
|
Sign up to set email alerts
|

Dangers of Clostridium perfringens food poisoning in psychiatric patients

Abstract: Clostridium perfringens food poisoning can be fatal in patients with chronic constipation. We report the investigation and management of a probable outbreak of C. perfringens food poisoning among psychiatric patients in Cape Town, South Africa, in 2013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Nevertheless, there are reports suggesting that type A is the cause of lethal haemorrhagic enteritis in several species, such as Panthera tigris altaica (Siberian tiger), Panthera leo (lion) [10], Vulpes vulpes (red fox) [22], Loxodonta africana (elephant) [23], Selenarctos thibetanus (Asian black bear) [24] and Papio hamadryas (hamadryas baboon) [25]. Previous studies have suggested that factors other than the toxinotype may be associated with the occurrence of enteric disease caused by C. perfringens type A in animals and humans, such as stress, dysregulation of the intestinal microbiota, and parasitic and viral infections [5,18,22,[24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are reports suggesting that type A is the cause of lethal haemorrhagic enteritis in several species, such as Panthera tigris altaica (Siberian tiger), Panthera leo (lion) [10], Vulpes vulpes (red fox) [22], Loxodonta africana (elephant) [23], Selenarctos thibetanus (Asian black bear) [24] and Papio hamadryas (hamadryas baboon) [25]. Previous studies have suggested that factors other than the toxinotype may be associated with the occurrence of enteric disease caused by C. perfringens type A in animals and humans, such as stress, dysregulation of the intestinal microbiota, and parasitic and viral infections [5,18,22,[24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are reports suggesting that type A is the cause of lethal haemorrhagic enteritis in several species, such as Panthera tigris altaica (Siberian tiger), Panthera leo (lion) [8], Vulpes vulpes (red fox) [18], Loxodonta africana (elephant) [19], Selenarctos thibetanus (Asian black bear) [20] and Papio hamadryas (hamadryas baboon) [21]. Previous studies have suggested that factors other than the toxinotype may be associated with the occurrence of enteric disease caused by C. perfringens type A in animals and humans, such as stress, the dysregulation of the intestinal microbiota, and parasitic and viral infections [5,15,18,[20][21][22][23][24][25][26][27][28]. In other words, C. perfringens type A is a facultative bacterium, meaning it is primarily commensal but can cause disease if the gut environment is disturbed or the host is stressed or otherwise immunocompromised.…”
Section: Discussionmentioning
confidence: 99%
“…Although symptoms of this food poisoning are typically limited to diarrhea and abdominal cramps that self-resolve within 24 h, fatalities can occur in the elderly ( 21 ). More recently, it has become recognized that type F food poisoning can also be lethal in younger, physically healthy individuals suffering from medication-induced severe constipation or fecal impaction at the time of infection by a type F strain ( 22 24 ). Those preexisting conditions are thought to block the intestinal flushing effects of CPE-induced diarrhea, leading to a prolonged contact between CPE and the intestines ( 22 ) that likely increases disease severity.…”
Section: Introductionmentioning
confidence: 99%